Application of the MADS classification system in a "mega mammoth" stent trial: Feasibility and preliminary clinical implications. Issue 1 (5th October 2018) - Katsikis, Athanasios; Chichareon, Ply; Cavalcante, Rafael; Collet, Carlos; Modolo, Rodrigo; Onuma, Yoshinobu; Stankovic, Goran; Louvard, Yves; Vranckx, Pascal; Valgimigli, Marco; Windecker, Stephan; Serruys, Patrick W.
Abstract: Objectives and Background: We attempted to test the feasibility of application of the MADS classification system in the largest stent trial to date and evaluate the preliminary clinical implications of this approach. Methods: In the randomized GLOBAL LEADERS trial, testing two different antiplatelet strategies in patients undergoing PCI with bivalirudin and biolimus‐eluting stents, the e‐CRF was dedicated to bifurcation treatment according to the MADS classification. Based on this e‐CRF, the techniques used for bifurcations treatment in GLOBAL LEADERS were described and compared with two large, all‐comer registries of bifurcations treatment (I‐BIGIS and COBIS), used as historical controls. Results: Among 15, 991 patients enrolled in the trial, 22, 921 lesions treated at the index and staged procedure were available for analysis and 2, 757 of these lesions were bifurcations and 7 were trifurcation lesions. The e‐CRF‐based MADS classification was achieved in 2, 757 of these lesions (100%). 80.3% of bifurcations were treated using a single stent, 18.9% using 2 stents and 0.7% using 3 stents. Overall, the "main across side first" approach (A) was used in 77.4% with the "side branch first" approach (S) being the second most frequently used technique (10.2%). A single stent was used in the majority of the "A" approach (87.9%). A reduction in the use of 2‐stent techniques (from 33.9 to 18.9%) was observed between GLOBAL LEADERS and I‐BIGIS. The "A" approach was the most frequently used technique in GLOBAL LEADERS, while in COBIS the "S" strategy was most frequently employed. Conclusions: Application of the MADS classification through an e‐CRF was feasible in the largest stent trial today and provided useful information about the trends observed overtime in the treatment of bifurcation lesions.